2010
DOI: 10.1200/jco.2009.23.4534
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Adult Survivors of Childhood Cancer: The Swiss Childhood Cancer Survivor Study

Abstract: Results show that childhood cancer survivors, on average, have less psychological distress than a norm population but that the proportion of survivors at risk for high psychological distress is disproportionally large. Monitoring psychological distress in childhood cancer survivors may be desirable during routine follow-up, and psychological support should be offered as needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
157
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(177 citation statements)
references
References 36 publications
14
157
6
Order By: Relevance
“…It is widely recognized that life-threatening and traumatic experiences have a radical impact on a person's existence, redefining priorities, objectives, and perceptions [5]. They can lead to posttraumatic stress and other emotional difficulties such as depression, somatization, and anxiety [6][7][8][9], but they can also bring positive experiences. Tedeschi the struggle with highly challenging life circumstances [10].…”
Section: Introductionmentioning
confidence: 97%
“…It is widely recognized that life-threatening and traumatic experiences have a radical impact on a person's existence, redefining priorities, objectives, and perceptions [5]. They can lead to posttraumatic stress and other emotional difficulties such as depression, somatization, and anxiety [6][7][8][9], but they can also bring positive experiences. Tedeschi the struggle with highly challenging life circumstances [10].…”
Section: Introductionmentioning
confidence: 97%
“…Psychosocial outcomes include depression and depressive symptoms, social withdrawal, cognitive impairment (Costa, 2010), poor academic achievement, and lower employment status (Lund, Schmiegelow, Rechnitzer, & Johansen, 2011;Michel, Rebholz, von der Weid, Bergstraesser, & Kuehni, 2010).…”
mentioning
confidence: 99%
“…Several studies suggested that 20-30% of survivors report moderate-to-severe psychological distress [6][7][8][9]. They reported poorer mental health than their siblings [10] and were twice as likely to report clinical levels of emotional distress compared with their siblings [11][12][13].…”
Section: Introductionmentioning
confidence: 97%